Walking gait changes after stepping-in-place training using a foot lifting device in chronic stroke patients - Murata, Kanichirou (J Phys Ther Sci, 2016)
[Purpose] The goal of this study was to investigate the efficacy of stepping-in-place training using a foot lifting assist device on the walking gait of chronic hemiparetic stroke patients. [Subjects] Seven patients with chronic hemiplegic stroke (age 80.9±4.9 years) who were attending a local adult daycare facility participated in this study. [Methods] The participants had 2 or 16 weeks of intervention after a baseline period of 2 weeks. Evaluations were performed before the baseline period and before and after the intervention period. The evaluation consisted of a two-dimensional motion analysis of walking and stepping-in-place exercises and a clinical evaluation. [Results] Walking speed increased in three participants after 2 or 16 weeks of intervention. The swing phase percentage increased in the paretic gait cycle, and the time from non-paretic heel contact to paretic heel off decreased during stepping-in-place in these participants. [Conclusion] Given that the transition from the support phase support to the swing phase was shortened after the intervention, the stepping-in-place exercise using the device designed for this study may improve the muscle strength of the lower limb and coordination in the pre-swing phase of the paretic limb.